Factors of real aspect, empathy, confidence, responsivity, reliability that affect community satisfaction in services in Belawang district office, Barito regency, Kuala - Susanti, Heni; Widiaswari, Roro Rukmini; Normajatun, Normajatun (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to determine "what are the factors that influence community satisfaction with services at the Belawang District Office, Barito Kuala Regency, seen from the aspects of tangible (touchable), realible (reliable), responsiveness (responsiveness), assurance (guarantee), and empathy (empathy)?" This research uses a descriptive design with quantitative methods. The data sources used are population and sample. Data collection techniques using literature, observation, interviews, documentation, and questionnaires The results obtained in this study, namely the factors that most influence community satisfaction in the Belawang District Office, can be seen from the real, convincing, and empathetic aspects. Because it is carried out and carried out properly and in accordance with the expectations of the community, so that community satisfaction with services will increase. However, in contrast to the responsiveness and reliability aspects, it does not affect community satisfaction because its application is not in accordance with what is expected by the community, so that it can reduce the level of community satisfaction but still affect satisfaction.